2017
DOI: 10.21472/bjbs.040708
|View full text |Cite
|
Sign up to set email alerts
|

Antihyperlipidemic and hypolipidemic properties of Tacca leontopetaloides (L.) Kuntze (Dioscoreales: Dioscoreaceae) tuber’s aqueous extracts in the rats

Abstract: Abstract. Tubers of Tacca leontopetaloides (L.) Kuntze (Dioscoreales: Dioscoreaceae) play an important role in food substitution during the periods of food shortage in occidental and central Africa. It is also used in traditional medicine for the treatment of the diarrhea, dysentery, stomach evil, viral hepatitis and the infection of guinea worn. This study attempted to evaluate the antihyperlipidemic and hypolipidemic properties of aqueous extracts of the tubers of T. leontopetaloides in rats. For this experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…The increase in the level of transaminases (ALT and AST) has also been observed in liver disorder [33][34][35][36]. These results are in agreement with those of [37,38] who reported that the ethanolic and methanolic extracts of Alchornia cordifolia leaves cause an increase in the activity of transaminases.…”
Section: Discussionsupporting
confidence: 84%
“…The increase in the level of transaminases (ALT and AST) has also been observed in liver disorder [33][34][35][36]. These results are in agreement with those of [37,38] who reported that the ethanolic and methanolic extracts of Alchornia cordifolia leaves cause an increase in the activity of transaminases.…”
Section: Discussionsupporting
confidence: 84%
“…Induction of hyperlipidemia in the rats was achieved by feeding HFD formulated according to the protocol described by Aissatou et al [32], with some modi cations. The detailed formulations of the different diets are given in Table 1.…”
Section: Induction Of Hyperlipidemia Using High-fat Dietmentioning
confidence: 99%
“…Feces were collected daily for the evaluation of the excreted lipids. The faecal matter was then dried and crushed with the porcelain mortar into fine powder (Aïssatou et al, 2017). The total lipids were extracted using the Soxhlet apparatus, according to the Russian method described by Bourely (1982).…”
Section: Analysis Of Faecal Lipidmentioning
confidence: 99%